Kingdom. 5 - Hara, Yasuhisa, 1975- (VIZ Media, LLC, 2026)
The journey of young orphan Xin's rise to glory as a great general in the Qin kingdom's quest to do what has never been done before--unify China. Xin is a war orphan in a poor village in the kingdom of Qin. He has big dreams of becoming the Greatest General Under the Heavens, and when his best friend's life is cut short by political machinations, Xin finds himself on a quest to do what no one has ever done before--unify China. With Cheng Jiao's coup put to rest and Ying Zheng back on the throne, life soon returns to almost normal for Xin and Diao. Having declared his goal of uniting the seven kingdoms under one leader, Ying Zheng commences his conquest, and Xin finally gets his opportunity to fight on a real battlefield, rise in the ranks, and become one of the Greatest Generals Under the Heavens! His first step is starting out as a foot soldier in a war against the Kingdom of Wei. But he quickly learns just what it means to be a mere foot soldier on the front lines against one of the Middle Kingdom's most terrifying armies.